Stage of infection with Mycobacterium avium subsp. paratuberculosis impacts expression of Rab5, Rab7, and CYP27B1 in macrophages within the ileum of naturally infected cows - Wherry, Taylor L. T.; Heggen, Mark; Shircliff, Adrienne L.; Mooyottu, Shankumar; Stabel, Judith R. (Frontiers in Veterinary Science, 2023)
Macrophages are the preferential target of Mycobacterium avium subsp. paratuberculosis (MAP), the etiologic agent of ruminant paratuberculosis. Uptake of pathogens by intestinal macrophages results in their trafficking through endosomal compartments, ultimately leading to fusion with an acidic lysosome to destroy the pathogen. MAP possesses virulence factors which disrupt these endosomal pathways. Additionally, levels of serum vitamin D3 have proven relevant to host immunity. Dynamics of endosomal trafficking and vitamin D3 metabolism have been largely unexplored in bovine paratuberculosis. This study aimed to characterize expression of early and late endosomal markers Rab5 and Rab7, respectively, within CD68+ macrophages in frozen mid-ileum sections harvested from cows at different stages of natural paratuberculosis infection. Additionally, factors of vitamin D3 signaling and metabolism were characterized through expression of vitamin D3 activating enzyme 1-hydroxylase (CYP27B1), vitamin D3 inactivating enzyme 24-hydroxylase (CYP24A1), and vitamin D3 receptor (VDR) within CD68+ ileal macrophages. Cows with clinical paratuberculosis had significantly greater macrophage and MAP burden overall, as well as intracellular MAP. Total expression of Rab5 within macrophages was reduced in clinical cows; however, Rab5 and MAP colocalization was significantly greater in this group. Intracellular Rab7 colocalization with MAP was not detected in subclinical or Johne’s Disease negative (JD-) control cows but was present in clinical cows. Additionally, macrophage CYP27B1 expression was significantly reduced in clinical cows. Taken together, the results from this study show disparate patterns of expression for key mediators in intracellular MAP trafficking and vitamin D metabolism for cows at different stages of paratuberculosis.